Exploiting a natural resource in a poor country: The good, the bad and the ugly sides of the Kyrgyz Republic's gold mine - Richard Pomfret (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2018)
What is required for a poor country to turn a valuable resource endowment into a driver of development? The resource curse literature highlighted the importance of institutions and the nature of the resource, neither of which is a useful policy guide. A more recent literature views resource exploitation as a series of hurdles that must be negotiated: ensuring production, dividing revenues, and using the added public finance. The Kyrgyz Republic's Kumtor gold mine is a useful case study in that the country cleared the first hurdle but over almost a quarter century was embroiled in negotiating the second hurdle. The paper assesses the extent to which such problems are inevitable for a small poor country, and the consequences of an extended conflictual process.
urn:nbn:de:101:1-2018061908580306807530
Keywords: Q32; O53; L72; N55; 330; resource curse; minerals; Kyrgyzstan